2007
DOI: 10.1007/s11130-006-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Extrusion on Functional Properties and Mineral Dialyzability from Phaseolus Vulgaris Bean Flour

Abstract: The effects of extrusion conditions on cooking degree, flour dispersion viscosity and mineral potential availability of extruded bean flour were studied. Phaseolus vulgaris beans of the agronomic cultivar "Flor de mayo" were ground and dehulled to obtain grits and then extruded at different temperatures (140, 160 and 180 degrees C) and moisture contents (17, 20 and 23%), according to a bifactorial experimental design. Degree of cooking was estimated by water solubility (WS) and specific mechanical energy (SME)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
2
15
0
5
Order By: Relevance
“…Dextrinization is well known as the predominant mechanism of starch degradation during low moisture extrusion [37]. Therefore, the decreasing trend of WSI with FM was expected and in agreement with previous reports [43,49].…”
Section: Water Solubility Index Y Wsisupporting
confidence: 91%
See 1 more Smart Citation
“…Dextrinization is well known as the predominant mechanism of starch degradation during low moisture extrusion [37]. Therefore, the decreasing trend of WSI with FM was expected and in agreement with previous reports [43,49].…”
Section: Water Solubility Index Y Wsisupporting
confidence: 91%
“…The WSI determines the amount of soluble polysaccharide released from the starch granules after addition of excess water and is often used as an index of degradation of molecular components which is related to dextrinization [36,42,43]. The regression analysis performed in Table 5 indicated that AS and BT had positive linear effects on WSI (p<0.05) followed by the quadratic effects of FM and BT (p < 0.05).…”
Section: Water Solubility Index Y Wsimentioning
confidence: 99%
“…The olive phenols impart antioxidant and antimicrobial properties to different parts of the plant and are also responsible for the extent of browning in the fruit (Ghanbari et al 2012). These phenolic components also contribute towards the sensory and aromatic characteristics of the olive as well as impart pharmaceutical and physiological benefits (Bianchi 2003;Covas 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Combination of heat and shear forces also denatures proteins and disrupt the food matrix, thereby improving the digestibility of nutrients [9]. There are some recent reports about extrusion cooking of common beans [10][11][12][13], but only two references to our knowledge have been published on physical properties of Mexican common beans [14,15]. Rocha-Guzman et al [14] studied three Mexican cultivars stored under accelerated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated water absorption index (WAI) and bulk density, finding that ageing of beans was the most important factor in WAI. Drago et al [15] studied Flor de Mayo cultivar. They evaluated water solubility (WS) and mineral dialyzability, showing that temperature factor was the only significant variable in WS.…”
Section: Introductionmentioning
confidence: 99%